Evaluation of DAZ1 Gene Expression in Spermatogenic Failure among Infertile Non-Obstructive Azoospermic Iraqi Males - I Abd Ali Al-Humairi; HA Karbal; AA Abid Albdairi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Non-obstructive azoospermia (NOA) is one of the causes of male infertility. Male infertility can be induced by changes in the expression pattern of a significant number of genes in spermatogenic cells. So, analysis of gene expression profiles of testicular tissues is essential in these patients. Since DAZ1 is an essential gene in spermatogenesis, this study aimed to evaluate the role of DAZ1 gene expression in NOA Iraqi males. Methods: This cross-sectional study enrolled a total of 50 infertile men with NOA attending Teba IVF and genetic Centre from December 2018 to December 2019. All patients had bilateral testicular sperm aspirate (TESA) under local anesthesia and biopsy. The quantitative detection and gene expression analysis of DAZ1 were carried out using the qPCR technique. The correlations between DAZ1 expression levels, testicular spermatogenic patterns, and clinical hormonal indicators were evaluated. The patients' histological phenotype and hormonal profile were also evaluated in gene expression data. Findings: The mean age of the patients was 35.1±6.6 years. DAZ1 gene expression was different in faulty spermatogenesis testes. Hypospermatogenesis patients had the greatest expression level of DAZ1. DAZ1 transcript expression was significantly lower in the six spermatogenic samples without germ cells or Sertoli cells (p<0.05). Men with the worst histology (maturation arrest and no germ cell and Sertoli cell) had higher mean blood FSH levels (36.6±3.9) (p<0.05). DAZ1 expression in testicular samples demonstrated significant positive correlation with the spermatogenic score (p<0.0001). Conclusion: The differential expression of spermatogenesis-related gene (DAZ1) across the various spermatogenic patterns suggests that this gene may be a molecular marker for NOA spermatogenesis assessment.